2016
DOI: 10.1371/journal.pone.0146595
|View full text |Cite
|
Sign up to set email alerts
|

Similar Spectral Power Densities Within the Schumann Resonance and a Large Population of Quantitative Electroencephalographic Profiles: Supportive Evidence for Koenig and Pobachenko

Abstract: In 1954 and 1960 Koenig and his colleagues described the remarkable similarities of spectral power density profiles and patterns between the earth-ionosphere resonance and human brain activity which also share magnitudes for both electric field (mV/m) and magnetic field (pT) components. In 2006 Pobachenko and colleagues reported real time coherence between variations in the Schumann and brain activity spectra within the 6–16 Hz band for a small sample. We examined the ratios of the average potential difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
2
14
0
1
Order By: Relevance
“…The peak power density within the gamma range over the left parahippocampal region also suggested that some residual of two receptor subtypes remained with affinities in the nanoMolar and milliMolar range. The increase in power within the gamma range after the applications of these two concentrations was between 0.3 and 0.5 μV 2 ·Hz -1 which is within the range of shifts in cerebral cortical activity that we have measured to be associated with consciousness and specific tasks [31, 32]. The laterality of the effect was clearly indicated.…”
Section: Discussionsupporting
confidence: 65%
“…The peak power density within the gamma range over the left parahippocampal region also suggested that some residual of two receptor subtypes remained with affinities in the nanoMolar and milliMolar range. The increase in power within the gamma range after the applications of these two concentrations was between 0.3 and 0.5 μV 2 ·Hz -1 which is within the range of shifts in cerebral cortical activity that we have measured to be associated with consciousness and specific tasks [31, 32]. The laterality of the effect was clearly indicated.…”
Section: Discussionsupporting
confidence: 65%
“…Our research [5,6] as well as the contributions of others [17,18] indicates that human beings on the surface of the planet are immersed in these fields. Direct measurement and coherence analyses indicate there is intermittent concordance about every 30 s for about one or two microstate durations (about 0.5 s) between the human QEEG and the Schuman conditions in real time measured here locally or in Italy [6].…”
Section: Discussionmentioning
confidence: 81%
“…The electrical component is ~1 mV per m and the magnetic field is ~1 pT (10 -12 T). These values are the same orders of magnitude generated by cerebral cortical activity [5,6].…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations